Electric power generation via asymmetric moisturizing of graphene oxide for flexible, printable and portable electronics - Liang, Yuan; Zhao, Fei; Cheng, Zhihua; Deng, Yaxi; Xiao, Yukun; Cheng, Huhu; Zhang, Panpan; Huang, Yaxin; Shao, Huibo; Qu, Liangti (Energy & environmental science, 2018)
Flexible power supplies that can harvest power from an ambient environment are of considerable interest for future portable electronics. However, the complex structure and costly functional material of current power generators hinder their further development and practical application. Here we demonstrate flexible, all-printable graphene oxide (GO) functionalized paper as a moisture-electric power generator with an induced voltage of up to 2 V. Such high voltage is achieved by asymmetric moisturizing of GO, which enables directional ion migration across the GO. This work demonstrates a low-cost, scalable, lightweight and bendable power generator, opening up new possibilities for significantly expanding the application domain of graphene and reducing the cost of portable electronics.